2020
DOI: 10.1002/adem.202000087
|View full text |Cite
|
Sign up to set email alerts
|

Improved Adhesion of Different Environmental Barrier Coatings on Al2O3/Al2O3‐Ceramic Matrix Composites

Abstract: Among other things, the efficiency of a gas turbine is limited by its maximum service temperature, which is determined by the thermomechanical capabilities of the components in the hightemperature section of the turbine. Decades of research are therefore aiming for solutions that enable a further increase in the turbine inlet temperature. In the past years, the maximum service temperature could be drastically increased by the use of thermal barrier coatings (TBCs) and complex cooling systems. Unfortunately, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…intermetallics, segregation), compositional grading or solid-state diffusion mechanisms can further affect this adhesion strength. Similarly, the cleanliness, surface oxides on metallic substrates, and mechanicalinterlocking effects from interfacial surface roughness can dramatically affect this adhesion [42,43]. Friction or intrinsic lubricity controls the unlubricated wear performance of a coating.…”
Section: Materials Optimisationmentioning
confidence: 99%
“…intermetallics, segregation), compositional grading or solid-state diffusion mechanisms can further affect this adhesion strength. Similarly, the cleanliness, surface oxides on metallic substrates, and mechanicalinterlocking effects from interfacial surface roughness can dramatically affect this adhesion [42,43]. Friction or intrinsic lubricity controls the unlubricated wear performance of a coating.…”
Section: Materials Optimisationmentioning
confidence: 99%
“…Therefore, it is of key importance to investigate the structural integrity and durability of EBC/CMC systems. Reports on the mechanical performance and structural integrity of such systems can be found in the literature [14][15][16], and interfacial adhesion and toughness issues have recently been addressed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Gatzen et al demonstrated the feasibility of depositing YAP on an alumina CMC via very-low pressure plasma spraying with no pre-or post-processing steps [7]. This manufacturability is desirable for the longevity of the coatings and is in contrast to other coating/composite pairs that must undergo surface alterations or heat treatments for adequate adhesion [8].…”
Section: Introductionmentioning
confidence: 99%